Język przedstawiony, czyli świat współczesnej prozy - Kaniewska, Bogumiła (Poznańskie Spotkania Językoznawcze, 2015)
The article is dealing with the place taken by language reflection in modern literary theory. Poststructural breakthrough in the Humanities had become a period of opening up to new inspiration, and most of all to “language learning”. Much more important than the direct impact of the deconstruction was a change of consciousness: hereby the structuralist paradigm as the dominant way of talking about literature became exhausted. One academic discourse was replaced by the multitude of languages , and the multiplicity of rhetoric. The certainty of interpretation was replaced by interpretative doubts. That distrust embraced everything: not only the methodology, but the literature itself. A literary work ceased to be an objective structure, and its meaning a function of order. In this situation of discipline language, as art material, becomes the object of special attention of authors and researchers. The significance of language experiments is present in modern Polish prose, especially in prose by Wiesław Myśliwski.